A rare case of bilateral nasolabial cysts in a postpartum lady - Ramanathan Chandrasekharan; Ajoy Mathew Varghese; John Mathew; Gaurav Ashish (Wolters Kluwer Medknow Publications, 2014)
Nasolabial cyst, also known as Klestadt's cyst is an uncommon nonodontogenic cyst. Bilateral nasolabial cysts are rarer and less than 10 cases have been reported in the literature. Diagnosis is usually clinical and they present as slow-growing swellings in the nasolabial region causing cosmetic deformity and nasal obstruction. A postpartum lady presented with bilateral swelling of the cheeks. Excision was done via a sublabial approach. She is asymptomatic one year after surgery. Nasolabial cysts are developmental but usually noticed after a trauma. There is no data relating the cysts to pregnancy.